Normas internacionales de inversión en procedimientos de arbitraje internacional y tratados de inversión (2018)
Due to the significant importance of foreign investment in the economic growth of countries, especially developing countries, the purpose of this research is to review the international standards of investment in international arbitration procedures and investment treaties which have been very effective in removing investment barriers, as well as protecting and attracting more foreign investors in host states. The research method used in this research is descriptive-analytical using library resources. The present study, by describing and analyzing concepts and examples and methods of enforcement of international standards of investment in bilateral and multilateral investment treaties as well as the international arbitration procedure, has concluded that these standards are very flexible and dynamic,and they evolve over time.